Koala Biovar of Chlamydia pneumoniae Infects Human and Koala Monocytes and Induces Increased Uptake of Lipids In Vitro - Coles, Katie A. (American Society for Microbiology, 2001)
We examined the ability of the koala biovar of Chlamydia pneumoniae to infect both Hep-2 cells and human monocytes and the effect of infection on the formation of foam cells. The koala biovar produced large inclusions in both human and koala monocytes and in Hep-2 cells. Koala C. pneumoniae induced foam cell formation with and without added low-density lipoprotein, in contrast to TW183, which produced increased foam cell formation only in the presence of low-density lipoprotein.